Management of external telephone contacts at a tertiary paediatric nephrology centre – a trainee-led service improvement project. (24th May 2012) - Minson, S; Jones, H; Shute, R; Shroff, R; Hothi, D
Abstract : Background and aims: A significant bulk of the registrar's workload is spent dealing with telephone calls from parents, young people, community teams and paediatricians working at DGHs. In our paediatric nephrology department we wanted to improve the management of such calls. The current practice was suffering from poor continuity of documentation, especially in cases where multiple calls about a single child had taken place, and poor handover within our internal team. We undertook a trainee-led service improvement project to review the process. Methods: We formally audited our current practice over a 2 week period to assess the volume, type and frequency of calls and review the documentation of new and frequent telephone consultations on the same child. Following the audit we worked with the medical team and clerical staff to create a proforma for collecting clinical data and a filing system to improve continuity of documentation between registrar shifts. The proforma and filing system were then introduced for a 6-week trial period and the process of managing outside calls was re-audited by the same registrar team. Results: Our starting audit of telephone consultations showed that the majority of calls (70%) were from paediatric teams at other hospitals and over the 2 week period multiple calls were registered on the same patients. Overall documentation was poor, limited and in many instances (60% of follow-up calls) previous clinical information and advice given was not available for subsequent calls. After introducing the new proforma we re-audited external calls and found clearer documentation and significantly reduced instances (<5%) where previous telephone consultation notes were unavailable. Conclusions: We describe a simple trainee-led service improvement project that produced a positive result to the way telephone calls were managed in our centre. This improved the quality of care provided to patients whose care we share with other hospitals. We also achieved an improvement to the service provided to our colleagues working at other centres, improving efficiency by reducing the need to repeat clinical information. Finally, the new system actually improved time management for our internal team owing to improved documentation allowing more simple and effective handover of clinical information.